The Certainty of Uncertainty: Taiwanese Public Opinion on U.S.–Taiwan Relations in the Early Trump Presidency. (December 2019) - Wu, Chung-li; Lin, Alex Min-Wei
The election of Donald Trump has injected new uncertainties into the conduct of U.S. foreign affairs in Asia. For Taiwan, regional security is challenging because it must simultaneously deal with an increasingly belligerent China and an America led by the unconventional Trump. Based on public opinion data, this study analyzes how the Taiwanese public perceives the state of U.S.–Taiwan relations, and how certain they are about America's overall commitment to Taiwan in this era. Results indicate that people in their 20s, pan-Green partisans, and those favoring Taiwan independence perceive U.S.–Taiwan relations to be better under President Trump. Moreover, supporters of the pan-Green coalition and of Taiwan independence, together with the more "ambivalent" respondents, likewise feel more certain about America's commitment to Taiwan's security. On the contrary, pan-Blue partisans and Taiwanese citizens with mainland Chinese ethnicity are generally more pessimistic and skeptical about U.S.–Taiwan ties and partnership with Trump in the White House.